Statistical Assessment of the Impact of Economic Globalization on the Structures of Output and Employment of the Processing Industry - Sozanskyy, L. Yо. (Statistics of Ukraine, 2024)
Verification of the impact of economic globalization on the functioning of industry is one of the debatable issues of economic science. Proponents of Ricardo’s theory of comparative advantages in economic globalization see the possibility of delineating the comparative advantages of countries in international trade. Instead, according to Keynes’s ideas, economic globalization causes increased economic dependence and a decrease in the self-sufficiency of countries. At the same time, insufficient attention has been paid to the impact of economic globalization on the structural indicators of the processing industry. In view of this, the study of the impact of economic globalization on the structure of output and employment of the processing industry has significant fundamental and applied importance. The purpose of the article is a statistical assessment of the relationships and modeling of the impact of economic globalization on the structures of output and employment of the processing industry. The study was based on the application of the data of the 20-year trend of the shares of production in the output in the employment of the processing industry of Poland, Germany, France and Italy and methods of correlation and regression analysis. Achieving the research goal was carried out in three stages. At the first stage, the amount of economic globalization was identified and the level and dynamics of the economic globalization index (de facto) were analyzed. Thanks to this, the countries that are conditionally open and closed to economic globalization have been determined. At the second stage, the author’s hypothesis was empirically proven that there is mostly a high or very high direct (for dominant industries) or inverse (for other industries) correlation between the economic index (de facto) and the shares of production in the production and employment structures of the processing industry. At the third stage, regression models were built, with the help of which the magnitude of the influence of the economic (de facto) index on the shares of production in the production and employment structures of the processing industry of Poland, Germany, France and Italy was determined, and the necessary analytical conclusions and explanations were made.